Teachers in Lebanon : Understanding the Quality of Teachers’ Instructional Practices and Performance - World Bank (Washington, DC, 2022)
This report presents detailed findings of a teacher performance study in Lebanon, one of four studies carried out under the Research for Results (R4R) program, a partnership between the Lebanese Ministry of Education and Higher Education and Development Partners. The objective of the research for results (R4R) initiative is to carry out a comprehensive review of education service delivery in Lebanon and recommend effective policy measures to improve the quality of teaching and, ultimately, student learning outcomes. As Lebanon continues to suffer from challenges in education from past and recent crises studying and measuring the quality of teaching instruction can be used as a guide for school leadership programs, teacher professional development trainings - including new curriculum design and effective lesson preparation. Designing policies that strengthen teaching practices is a crucial step in improving education quality for all in Lebanon. This report focuses on assessing teachers’ instructional quality in teaching Arabic language, foreign language (English or French), and Mathematics (English or French), comprising 707 teachers in a total of 146 schools from a nationally representative sample across Lebanon in grades 4 and 7, in public (morning and afternoon shifts), free private and fee-based private schools, using the CLASS observation tool.